1998
DOI: 10.1086/301868
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping of Ossification of the Posterior Longitudinal Ligament of the Spine

Abstract: Ossification of the posterior longitudinal ligament of the spine (OPLL) is recognized as a common disorder among Japanese and throughout Asia. Estimates of its prevalence are in the range of 1. 9%-4.3%. Although its etiology is thought to involve a multiplicity of factors, epidemiological and family studies strongly implicate genetic susceptibility in the pathogenesis of OPLL. In this study we report an identification of a predisposing locus for OPLL, on chromosome 6p, close to the HLA complex. The evidence fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(99 citation statements)
references
References 28 publications
(30 reference statements)
2
96
0
1
Order By: Relevance
“…It is unclear why thoracic myelopathy more often develops in middleaged people compared to cervical myelopathy patients. OLF and OPLL, the major causes of thoracic myelopathy, might be associated with some genetic factors (Koga et al 1998;Yamamoto et al 2002). The thoracic spine is naturally kyphotic and the spinal cord runs anterior of the spinal canal, which suggests the cord is more easily damaged from the anterior side.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why thoracic myelopathy more often develops in middleaged people compared to cervical myelopathy patients. OLF and OPLL, the major causes of thoracic myelopathy, might be associated with some genetic factors (Koga et al 1998;Yamamoto et al 2002). The thoracic spine is naturally kyphotic and the spinal cord runs anterior of the spinal canal, which suggests the cord is more easily damaged from the anterior side.…”
Section: Discussionmentioning
confidence: 99%
“…Many collagen genes have been studied, including human collagen a2 gene (COL11A2). Koga et al 61 showed that this gene, located on chromosome 6p close to the human leukocyte antigen region, is strongly associated with OPLL. Retaining exon 7 together with removal of exon 6 observed in intron 6(-4A) in the COL11A2 gene could play a protective role in the ectopic ossification process.…”
Section: Pathogenesismentioning
confidence: 99%
“…OPLL patients show ectopic bone formation in the posterior longitudinal ligament, which compresses the spinal cord leading to various neurological symptoms. Despite the late onset (average age of onset is 50 years), OPLL has a strong genetic background as shown in classical epidemiological studies and by an estimate of relative risk to siblings of ϳ10 (2,3). Because genetic factors appear to play crucial roles in the etiology of OPLL, genetic screenings to identify susceptibility are important.…”
mentioning
confidence: 99%